2016
DOI: 10.3748/wjg.v22.i31.7091
|View full text |Cite
|
Sign up to set email alerts
|

Application of stapling devices in liver surgery: Current status and future prospects

Abstract: The liver is a vascular-rich solid organ. Safe and effective dissection of the vessels and liver parenchyma, and control of intraoperative bleeding are the main concerns when performing liver resection. Several studies have confirmed that intraoperative blood loss and postoperative transfusion are predictors of postoperative morbidity and mortality in liver surgery. Various methods and instruments have been developed during hepatectomy. Stapling devices are crucial for safe and rapid anastomosis. They are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Currently, laparoscopic hepatectomy often requires both an experienced surgeon and expensive equipment, such as the Endo-GIA stapling system (Consten et al 2008;Scuderi and Troisi 2014;Yao and Wu 2016), a saline-coupled bipolar sealer (Sastry et al 2019), an ultrasonic scalpel (Chai et al 2018;Kim et al 2017), a laparoscopic laser (Ellebrecht et al 2018) and a microwave applicator (Chong et al 2018;Dimitri et al 2019;Shen et al 2018). These factors restrict the widespread use of hepatic lobectomy in veterinary clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, laparoscopic hepatectomy often requires both an experienced surgeon and expensive equipment, such as the Endo-GIA stapling system (Consten et al 2008;Scuderi and Troisi 2014;Yao and Wu 2016), a saline-coupled bipolar sealer (Sastry et al 2019), an ultrasonic scalpel (Chai et al 2018;Kim et al 2017), a laparoscopic laser (Ellebrecht et al 2018) and a microwave applicator (Chong et al 2018;Dimitri et al 2019;Shen et al 2018). These factors restrict the widespread use of hepatic lobectomy in veterinary clinics.…”
Section: Discussionmentioning
confidence: 99%
“…This is a relatively low-cost procedure. However, liver surgeons are prone to using vascular staplers to limit transection durations and shorten the portal pedicle closure time, or they may even perform no occlusion ( 7 , 16 ). Transection of the hepatic veins or Glisson's pedicles using vascular staplers has been widely used in multiple surgical liver centers ( 2 , 9 , 10 , 17 ).…”
Section: Open Lrmentioning
confidence: 99%
“…In addition, this decreases the need for portal triad clamping during liver ischemic reperfusion injury ( 2 , 10 ). Previous systemic reviews proposed that stapler devices should be used in open or laparoscopic LR and reported that up to nine vascular staplers are used for parenchymal transection in laparoscopic liver surgery ( 7 , 11 ). Using vascular staplers may improve the speed and safety of ligation in both inflow and outflow vessels, thereby facilitating LR ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The vessels are ligated with absorbable suture and hemostasis of larger lacerations can be obtained with sutures and patches of omentum [20]. Liver stapling allows for transection and ligation of liver panenchyma, arteries, veins, and ducts in a quick, safe, and efficient manner and is useful in larger sections that require surgical excision [16]. The Pringle maneuver, which clamps the hepatoduodenal ligament and therefore the hepatic artery, portal vein, and common bile duct, can be performed for up to 1 h to limit blood flow through the liver and therefore more easily identify injuries [14].…”
Section: Intra-abdominal Explorationmentioning
confidence: 99%